2021
DOI: 10.3390/en14165116
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Air-Cathode Microbial Fuel Cells Performance under Different Serially and Parallelly Connected Configurations

Abstract: Microbial fuel cells (MFCs) have recently attracted more attention in the context of sustainable energy production. They can be considered as a future solution for the treatment of organic wastes and the production of bioelectricity. However, the low output voltage and the low produced electricity limit their applications as energy supply systems. The scaling up of MFCs both by developing bigger reactors with multiple electrodes and by connecting several cells in stacked configurations is a valid solution for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Parallel system at the same time gave very high current densities ranging from 0.1-0.3 A/m 2 as voltage drop was observed to be minimum here with an internal resistance of around 40Ω compared to 5000Ω as offered by series connected system (Table 6). These are in con nement with other studies [(Vilajeliu-Pons et al 2017), (Minutillo et al 2021)] and it could be concluded that the rate of ohmic losses increases rapidly with current density for systems stacked in series compared to systems stacked in parallel. It can also be seen here that despite cathodic modi fcation with catalyst, the activation overpotential remains high in case of series connected cells, rendering a system of very less current density though open circuit potential was high.…”
Section: Performance Of Stacked Mfcsupporting
confidence: 91%
See 1 more Smart Citation
“…Parallel system at the same time gave very high current densities ranging from 0.1-0.3 A/m 2 as voltage drop was observed to be minimum here with an internal resistance of around 40Ω compared to 5000Ω as offered by series connected system (Table 6). These are in con nement with other studies [(Vilajeliu-Pons et al 2017), (Minutillo et al 2021)] and it could be concluded that the rate of ohmic losses increases rapidly with current density for systems stacked in series compared to systems stacked in parallel. It can also be seen here that despite cathodic modi fcation with catalyst, the activation overpotential remains high in case of series connected cells, rendering a system of very less current density though open circuit potential was high.…”
Section: Performance Of Stacked Mfcsupporting
confidence: 91%
“…The parallel series system was found to perform better than series connected system, but offered higher resistance compared to parallel connected system as well as uidically connected multielectrode system, unlike noticed in other scaled up systems (Minutillo et al 2021) where this mixed circuitry was found to reduce the internal resistance substantially as shown in Table 6. The uidically connected parallel system attained a stepping up of current and power by factors of 5.5 and 5.2 respectively while the parallel series system could attain only 4.6 and 1.5 factor increase in power and current.…”
Section: Performance Of Stacked Mfcmentioning
confidence: 85%
“…where R ext was the resistance of an external resistor whose value was equal to 1000 Ω. V (mV) is the voltage capacity of the closed-circuit voltage of the MFC unit. The following sets of electrochemical equations will be taking place in both the anodic and cathodic chambers of the MFC unit as the fundamental principle of microbial electrochemistry taking place during the operation phases within the MFC, sourced [19,33,[39][40][41][42][43][44][45][46][47][48][49][50][51]. Organic Matter is subsequently oxidised by microbes, electrons and protons and carbon dioxide is produced.…”
Section: Mfc Experimental Materialsmentioning
confidence: 99%